1983
DOI: 10.1172/jci111057
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality in calcium release from skeletal sarcoplasmic reticulum of pigs susceptible to malignant hyperthermia.

Abstract: A B S T R A C T Two fractions of sarcoplasmic reticulum, one light (LSR) and one heavy (HSR), were isolated from gracilis muscle of control and malignant hyperthermia (MH)-susceptible pigs. Part of the gracilis muscle biopsy was used to compare the contracture sensitivity of the muscle to the calcium-releasing effects of caffeine on isolated SR membranes. Gracilis muscle of MH pigs was more sensitive to the contracture-producing effects of caffeine than control pig muscle. The caffeine dose-cumulative contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
9

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(50 citation statements)
references
References 31 publications
3
38
0
9
Order By: Relevance
“…Enhancement of CICR in patients with MH or in MH-susceptible pigs has also been demonstrated in FSR (22,67,123,174,193,201), [ 3 H]ryanodine binding to SR vesicles (91,174,267), and the single-channel activity of RyR1 (68,174,194,236,237,238). Although some studies failed to find increased Ca 2ϩ sensitivity of CICR (68,236,238), the maximum rate of Ca 2ϩ release was increased and, therefore, the absence of the increased Ca 2ϩ sensitivity does not rule out the possibility of the essential involvement of CICR in MH, as discussed below.…”
Section: B Malignant Hyperthermiamentioning
confidence: 91%
“…Enhancement of CICR in patients with MH or in MH-susceptible pigs has also been demonstrated in FSR (22,67,123,174,193,201), [ 3 H]ryanodine binding to SR vesicles (91,174,267), and the single-channel activity of RyR1 (68,174,194,236,237,238). Although some studies failed to find increased Ca 2ϩ sensitivity of CICR (68,236,238), the maximum rate of Ca 2ϩ release was increased and, therefore, the absence of the increased Ca 2ϩ sensitivity does not rule out the possibility of the essential involvement of CICR in MH, as discussed below.…”
Section: B Malignant Hyperthermiamentioning
confidence: 91%
“…A notable exception is found among the earliest work investigating the effect of the MH R615C mutation on Ca 2ϩ handling by isolated SR membranes (13,24,25). Nelson and colleagues (13,24,25) …”
Section: Malignant Hyperthermia (Mh)mentioning
confidence: 99%
“…However, in comparison with the extensive investigations of the sensitivity of MHS RyR1 channels to cytosolic Ca 2ϩ and Mg 2ϩ , the effects of the MH R615C mutation on the luminal Ca 2ϩ sensitivity of the channel remain largely unexplored. A notable exception is found among the earliest work investigating the effect of the MH R615C mutation on Ca 2ϩ handling by isolated SR membranes (13,24,25). Nelson and colleagues (13,24,25) originally reported that the luminal Ca 2ϩ load required to trigger spontaneous SR Ca 2ϩ * This work was supported, in whole or in part, by National Institutes of Health Grants 1RO1HL75210 and RO1HL076433.…”
mentioning
confidence: 99%
“…Skeletal muscle sarcoplasmic reticulum from porcine diaphragm was prepared following the method given by I.e. (12). Crude membrane ffactions of different muscle types were isolated s described in 1. c. (8).…”
Section: Methodsmentioning
confidence: 99%